Differences in the Implementation of Campus Football Policy in Grassroots Schools in Tianshui, Gansu - Li, Yinglong (Pacific International Journal, 2025)
This study investigates the implementation of China’s national campus football policy in grassroots schools within Tianshui, Gansu Province, a region characterized by developmental disparities. Through a combination of interviews and case studies, the findings reveal significant urban-rural differences in policy execution. Key disparities are identified in infrastructure, coaching resources, curriculum integration, and management commitment. Urban schools generally benefit from better facilities, more specialized coaching, and systematic training structures, aligning more closely with national policy objectives. In contrast, rural schools face substantial challenges, including inadequate pitches, a shortage of qualified football teachers, and ad-hoc curriculum implementation, often limited to basic physical education. The analysis identifies that these differences stem primarily from uneven regional funding, a limited supply of qualified coaching talent, varying levels of administrative motivation, and differing socio-cultural attitudes towards sports among parents. The study concludes that without targeted interventions addressing these specific resource and motivational gaps, the policy risks reinforcing existing educational inequalities rather than achieving its goals of widespread youth development. Recommendations are provided for multi-level stakeholders to promote more equitable and effective policy implementation.